Effect of surface gallium termination on the formation and emission energy of an InGaAs wetting layer during the growth of InGaAs quantum dots by droplet epitaxy. (2nd April 2023) - Fricker, D; Atkinson, P; Jin, X; Lepsa, M; Zeng, Z; Kovács, A; Kibkalo, L; Dunin-Borkowski, RE; Kardynał, BE
Abstract: Self-assembled quantum dots (QDs) based on III–V semiconductors have excellent properties for applications in quantum optics. However, the presence of a 2D wetting layer (WL) which forms during the Stranski–Krastanov growth of QDs can limit their performance. Here, we investigate WL formation during QD growth by the droplet epitaxy technique. We use a combination of photoluminescence excitation spectroscopy, lifetime measurements, and transmission electron microscopy to identify the presence of an InGaAs WL in these droplet epitaxy QDs, even in the absence of distinguishable WL luminescence. We observe that increasing the amount of Ga deposited on a GaAs (100) surface prior to the growth of InGaAs QDs leads to a significant reduction in the emission wavelength of the WL to the point where it can no longer be distinguished from the GaAs acceptor peak emission in photoluminescence measurements. However increasing the amount of Ga deposited does not suppress the formation of a WL under the growth conditions used here.